2020
DOI: 10.3390/w12041184
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Evaluation of the Water Supply and Stormwater Management Performance of Retrofittable Domestic Rainwater Harvesting Systems

Abstract: Rainwater harvesting systems are often used as both an alternative water source and a stormwater management tool. Many studies have focused on the water-saving potential of these systems, but research into aspects that impact stormwater retention-such as demand patterns and climate change-is lacking. This paper investigates the short-term impact of demand on both water supply and stormwater management and examines future and potential performance over a longer time scale using climate change projections. To ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 16 publications
1
10
1
Order By: Relevance
“…A sensitivity analysis concerning household water demand is essential as it is often assumed that householders will exclusively use rainwater for their non-potable water needs when available. However, Quinn et al. (2020) showed that householders with a downstairs toilet connected to a conventional rainwater harvesting system did not use the water available to them as often as would be expected by the British Standards Institution (2013) .…”
Section: Discussionmentioning
confidence: 98%
“…A sensitivity analysis concerning household water demand is essential as it is often assumed that householders will exclusively use rainwater for their non-potable water needs when available. However, Quinn et al. (2020) showed that householders with a downstairs toilet connected to a conventional rainwater harvesting system did not use the water available to them as often as would be expected by the British Standards Institution (2013) .…”
Section: Discussionmentioning
confidence: 98%
“…For VGS, some literature demonstrates the potential of rainwater use [46,47], but detailed experimental investigation is scarce [48]. Rainwater harvesting systems have proven to be effective as partial substitutes for domestic water demand in oceanic zones [49], as well as in semi-arid climatic zones [50], but limiting factors include the unpredictability of precipitation patterns and the size of water storage systems, which may be prohibitive [14]. On the other hand, wastewater, particularly greywater, is produced daily and, hence, can provide a continuous stream of irrigation water once treated.…”
Section: The "Wicked Problem" Of Watermentioning
confidence: 99%
“…As described above, smart RWH systems are characterized by their ability to automatically release stored rainwater prior to rain events based on weather forecasts. There-fore, with reference to smart RWH approaches [8][9][10][11], the following digital uncertainties could be identified:…”
Section: Integrated Resilience Index For the Interlinked Systems Smart Rainwater Harvesting And Udnmentioning
confidence: 99%
“…However, detention efficiency is strongly dependent on user behavior and withdrawal quantities in relation to the detention volume. This can be a limitation especially for traditional systems, which are therefore referred to as uncontrolled RWH systems [6,11]. For example, higher withdrawal volumes empty RWH systems faster, therefore additional storage volumes can be provided for stormwater detention.…”
Section: Introductionmentioning
confidence: 99%